limh→0 f((6+h)−f(6)) / h ,when f(x)= √x -4
in Calculus Answers by

Your answer

Your name to display (optional):
Privacy: Your email address will only be used for sending these notifications.
Anti-spam verification:
To avoid this verification in future, please log in or register.

1 Answer

f(6)=√6-4. (6+h)-f(6)=6+h-(√6-4)=6-√6+4+h=10-√6+h.


I think the question should have been written:

lim h➝0 (f(6+h)-f(6)) / h, which makes better sense.

So we have (√(6+h)-4-(√6-4))/h=(√(6+h)-√6-4+4)/h=(√(6+h)-√6)/h.

We can write √(6+h) as √(6(1+(h/6)))=√6(1+(h/6))^½.

This approximates to √6(1+h/12)=√6+h√6/12 when h is small.

So (√(6+h)-√6)/h=(√6+h√6/12-√6)/h=√6/12 which can also be written √6/(2×6)=1/(2√6). This evaluates to 0.2041 approximately.

by Top Rated User (616k points)

Related questions

1 answer
1 answer
0 answers
asked Mar 17, 2013 in Calculus Answers by anonymous | 86 views
1 answer
Welcome to, where students, teachers and math enthusiasts can ask and answer any math question. Get help and answers to any math problem including algebra, trigonometry, geometry, calculus, trigonometry, fractions, solving expression, simplifying expressions and more. Get answers to math questions. Help is always 100% free!
82,260 questions
86,784 answers
3,660 users